LncRNA TATDN1 contributes to the cisplatin resistance of non-small cell lung cancer through TATDN1/miR-451/TRIM66 axis. Issue 3 (4th March 2019) - Wang, Linmei; Shang, Xueqin; Feng, Qingqing
ABSTRACT: Background: Chemoresistance has been considered to be a major obstacle for cancer therapy clinically. Long non-coding RNAs (LncRNAs) are asscociated with the development, prognosis and drug-resistance of non-small cell lung cancer (NSCLC). Whereas, the regulatory mechanism of lncRNA TATDN1 in the cisplatin resistance of NSCLC is still not clear. Methods: The expression of TATDN1, miR-451 and TRIM66 in NSCLC tissues and cell lines were detected by qRT-PCR or western blot. Immunohistochemistry (IHC) assay was performed for the detection of TATDN1 expression profile. 88 patients who underwent cisplatin treatment were followed up to 60-months for the analysis of survival rate. MTT and Flow cytometry analysis were performed for the assessment of cell survival rate, proliferation and apoptosis. Bioinformatics, Dual-Luciferase reporter were employed to analyze the interaction among TATDN1, miR-451 and TRIM66. Xenograft tumor model was constructed to verify the role of TATDN1 in NSCLC treated with cisplatin (DDP) in vivo . Results: TATDN1 and TRIM66 was significantly upregulated while miR-451 was downregulated in NSCLC tissues and cell lines, especially in DDP-resistant tumor tissues and cells. Survival rates of NSCLC patients with low TATDN1 expression were improved following DDP chemotherapy. TATDN1 upregulated TRIM66 expression via sponge for miR-451. Moreover, TATDN1 knockdown improved DDP-sensitivity in NSCLC patients by regulation of miR-451/TRIM66 axis. Finally, knockdown of TATDN1 improved the sensitivity of NSCLC to DDP in vivo . Conclusions: TATDN1 enhanced the DDP-tolerance of NSCLC cells by upregulating TRIM66 expression via sponging miR-451, hinting a novel regulatory pathway of chemoresistance in DDP-tolerant NSCLC cells and providing a potential therapeutic target for NSCLC patients with DDP-reistance.